The Influence Of Compensation And The Motivation Towards Organizational Culture: A Study On Gojek Indonesia - Agustriyana, Darwis; Kurniyanti Putri, Erika (International Journal of Psychosocial Rehabilitation, 2020)
Research This Aims To Know Compensation, Motivation, And Culture Organization On Pt. Application Works Children Nation (Gojek Indonesia) And To Know How Great Influence Between Compensation, Motivation, and Culture Organization At PT. Application Works Children Nation (Gojek Indonesia). Compensation That Given By Party Company Can Said Good Because Party Company Have Programs that Considered Interesting I.e., Give Incentives Additional Through Points GOPAY. Customer That Do Top-up GOPAY Through Driver Will Give Bonus Form Points That Can Collected by the Driver to Get Income Additional and Motivation That Owned by the Driver Can Said High Because Every Driver Have Spirit Work To Can Give Service Best To The Customer. Then Culture Organization That Applied by Company Already Good but Still There are Some Cheating—Cheating That Done by the Driver That Considered Harm Customer By Get Advantage. Method Research That Used, i.e., Method Descriptive-Verificative. Sample That Used on Research This I.e Driver Gojek In the city of Bandung. Processing Data Done with Regression Linear Multiple, Analysis Coefficient Correlation, Analysis Coefficient Determination, and Testing Hypothesis. Based Results Research Can Concluded That There is Influence Between Compensation Against Culture Organization on Pt. Application Works Children Nation (Gojek Indonesia) And There is Influence Between Motivation Against Culture Organization on Pt. Application Works Children Nation (Gojek Indonesia). And There is Influence A Together Between Compensation and Motivation Against Culture Organization on Pt. Application Works Children Nation (Gojek Indonesia).